Soft magnetic composite ferrite core and preparation method and application thereof
By using manganese oxide and copper oxide to replace nickel oxide in the process of preparing soft magnetic composite ferrite cores, and using a two-step pre-sintering process, the product consistency and performance problems caused by the differences in sintering processes are solved, and a low-cost and high-performance core preparation is achieved.
Patent Information
- Application Number
- CN202311251678.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-03-28
AI Technical Summary
In the process of preparing composite ferrite magnets, it is difficult to reasonably control the differences in sintering process between the components of different composite materials, resulting in poor product consistency and performance.
By replacing some nickel oxides with inexpensive manganese oxides and copper oxides with a two-step pre-sintering process, CuFe2O4 and MnFe2O4 are formed, thereby reducing the sintering temperature and improving product consistency and performance.
It effectively reduces the sintering temperature and production costs, improves the magnetic permeability, saturated magnetic induction strength and temperature stability of the product, and ensures process repeatability and product consistency.
Smart Images

Figure BDA0004470450200000101 
Figure BDA0004470450200000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnetic materials and relates to a soft magnetic composite ferrite core and a preparation method and application thereof. Background Art
[0002] Ferrite magnetic materials mainly include spinel, garnet and magnetoplumbite types of polycrystalline and single crystal ferrite materials. They have high resistivity, low loss, good dielectric properties and frequency characteristics. They are an important type of magnetic functional materials and are widely used in modern communications, military, electronics, information, chemical industry, biology, medicine and other fields.
[0003] Soft magnetic MnZn ferrite core materials have the characteristics of high initial magnetic permeability μi, high saturation magnetic induction intensity Bs and high temperature low loss Pcv, but the surface resistance is much lower than that of soft magnetic NiZn ferrite core materials. The surface resistance of soft magnetic MnZn ferrite core materials is generally only a few ohms to a few hundred ohms, while the surface resistance of soft magnetic NiZn ferrite core materials can usually reach more than 109 ohms, but the initial magnetic permeability μi, saturation magnetic induction intensity Bs and high temperature low loss Pcv of soft magnetic NiZn ferrite core materials are all worse than those of soft magnetic MnZn ferrite core materials.
[0004] CN103632794A discloses a composite soft magnetic material and a method for preparing the material. The composite soft magnetic material is composed of soft ferrite powder and soft magnetic alloy film. The composite material is compounded from powder materials and the ferrite powder is coated with metal materials to obtain composite electromagnetic properties. However, the method actually adopts a chemical plating process and still needs to be sintered to achieve ferritization. The problem of co-firing of the composite layer under unsuitable conditions cannot be avoided.
[0005] CN 111584206 A discloses a magnetic core and a preparation method thereof, an inductor and a filter. The anti-EMI magnetic core is manufactured by bonding and winding strips with different magnetic properties available on the market. The winding method is limited by the shape of the winding tooling and cannot manufacture flat or complex-shaped magnetic cores, so it is limited to circular ring-shaped magnetic cores used for filtering.
[0006] CN1587193A discloses a spinel ferrite material with low temperature coefficient, low loss and high saturation magnetic flux density, wherein the ferrite material has high initial magnetic permeability (800-900), low specific temperature coefficient (5-7×10 -6 ) manganese-nickel-zinc-copper ferrite, but its Curie temperature Tc is below 200℃ and its magnetic permeability is not high, less than 1000; this can no longer meet the requirements of the automotive electronics market; therefore, there is an urgent need to develop a new type of high magnetic permeability MnNiZnCu composite soft magnetic ferrite with a Curie temperature exceeding 200℃, a low specific temperature coefficient and a high Bs.
[0007] In the process of preparing the composite ferrite magnets in the above scheme, there are still problems such as large differences in sintering processes among the components of different composite materials, which are difficult to reasonably control. Summary of the invention
[0008] The purpose of the present invention is to provide a soft magnetic composite ferrite core and its preparation method and application. The present invention uses cheap manganese oxide and copper oxide to replace part of nickel oxide, controls two-step pre-sintering, and can generate CuFe 2 O 4 and MnFe 2 O 4 , thereby reducing the subsequent sintering temperature, reducing costs and improving product consistency.
[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a method for preparing a soft magnetic composite ferrite core, the preparation method comprising the following steps:
[0011] (1) grinding and mixing the main materials and then pre-burning them to obtain a pre-burned material;
[0012] (2) mixing the pre-sintered material with the additive, grinding it, and then performing a molding and sintering process to obtain the soft magnetic composite ferrite core;
[0013] The main materials include iron oxide, zinc oxide, nickel oxide, manganese oxide and copper oxide, and the pre-firing process includes one-step pre-firing and two-step pre-firing.
[0014] In the preparation process of the soft magnetic composite ferrite core of the present invention, manganese oxide and copper oxide are used to replace nickel oxide, so that the cost of raw materials is reduced. In the one-step pre-sintering process, copper oxide can form CuFe with iron oxide. 2 O 4 , so that spinel ferrite can be formed at a very low temperature, and manganese oxide and iron oxide form spinel MnFe during the two-step pre-sintering process. 2 O 4 This is very beneficial for promoting the subsequent sintering reaction and can effectively reduce the sintering temperature. Due to the low sintering temperature, a lot of energy is saved, the design requirements of the sintering equipment are also reduced, and the production cost is further reduced. Due to the wide pre-sintering and sintering temperature range and the absence of atmosphere protection, the process repeatability and product consistency are very good.
[0015] Preferably, the iron oxide comprises Fe 2 O 3 .
[0016] Preferably, the zinc oxide comprises ZnO.
[0017] Preferably, the nickel oxide comprises Ni 2 O 3 .
[0018] Preferably, the manganese oxide comprises MnO and / or Mn 3 O 4 .
[0019] Preferably, the copper oxide comprises CuO.
[0020] Preferably, based on the molar amount of the main material as 100%, the molar fraction of the iron oxide is 52.5-55.6 mol%, for example, 52.5 mol%, 53 mol%, 54 mol%, 55 mol% or 55.6 mol%.
[0021] Preferably, based on 100% molar amount of the main material, the molar fraction of the zinc oxide is 26.5-34 mol%, for example, 26.5 mol%, 27 mol%, 39 mol%, 30 mol% or 34 mol%.
[0022] Preferably, based on the molar amount of the main material being 100%, the molar fraction of the nickel oxide is 9-12 mol%, for example, 9 mol%, 10 mol%, 11 mol% or 12 mol%.
[0023] Preferably, based on the molar amount of the main material as 100%, the molar fraction of the manganese oxide is 1.4-3.5 mol%, for example: 1.4 mol%, 2 mol%, 2.5 mol%, 3 mol% or 3.5 mol%.
[0024] Preferably, based on the molar amount of the main material as 100%, the molar fraction of the copper oxide is 2-8 mol%, for example, 2 mol%, 3 mol%, 5 mol%, 6 mol% or 8 mol%.
[0025] Preferably, the grinding and mixing method in step (1) includes ball milling.
[0026] Preferably, the grinding and mixing time is 2 to 4 hours, for example, 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours.
[0027] Preferably, the mixed material is dried after the grinding and mixing.
[0028] Preferably, the temperature of the one-step pre-firing is 680-720°C, for example, 680°C, 690°C, 700°C, 710°C or 720°C.
[0029] Preferably, the one-step pre-burning time is 1 to 3 hours, for example, 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours.
[0030] Preferably, the temperature of the second-step pre-sintering is 800-900°C, for example, 800°C, 820°C, 850°C, 880°C or 900°C.
[0031] Preferably, the second-step pre-burning time is 1 to 3 hours, for example, 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours.
[0032] Preferably, the additive in step (2) includes nano Bi 2 O 3 and submicron SnO 2 .
[0033] The present invention uses nano Bi 2 O 3 and submicron SnO 2 As an additive, Bi 2 O 3 The powder has a nanometer size, a large specific surface area, and a relatively high surface energy. It can form a liquid phase at a very low temperature, promote sintering, and effectively reduce the sintering temperature. Using an appropriate amount of submicron SnO 2 As a flux, although it can improve high-frequency characteristics, it reduces the quality factor of the low-frequency band; and the appropriate amount of Bi 2 O 3 The addition of flux is the opposite, which is beneficial to reducing the loss in the low frequency band, but not conducive to reducing the loss in the high frequency band. Moreover, although the single flux addition method can reduce the sintering temperature to a certain extent, the effect is not as good as Bi. 2 O 3 and SnO 2 The quality factor of ferrite decreases with the increase of the added amount. 2 O 3 and submicron SnO 2 The combined addition as an additive flux can effectively reduce the sintering temperature to below 1100°C, and both high-temperature and low-temperature magnetic permeabilities are greatly improved, with good temperature stability characteristics.
[0034] Preferably, based on the mass of the main material being 100%, the Bi 2 O 3 The mass of is 0.1-2.5%, for example: 0.1%, 0.5%, 1%, 2% or 2.5%, etc.
[0035] Preferably, based on the mass of the main material being 100%, the SnO2 The mass of is 0.03-0.5%, for example: 0.03%, 0.05%, 0.1%, 0.25% or 0.5%, etc.
[0036] Preferably, the Bi 2 O 3 and SnO 2 The mass ratio is 1:(0.1~1.2), for example: 1:0.1, 1:0.4, 1:0.8, 1:1 or 1:1.2, etc.
[0037] Preferably, the grinding treatment in step (2) comprises ball milling.
[0038] Preferably, the grinding treatment time is 3 to 15 hours, for example: 3 hours, 5 hours, 8 hours, 10 hours or 15 hours.
[0039] Preferably, the average particle size of the material obtained after the grinding process is less than 1 μm.
[0040] Preferably, the molding and sintering treatment in step (2) includes drying the ground material, mixing it with polyvinyl alcohol, pressing it into shape, and then sintering it to obtain the soft magnetic composite ferrite core.
[0041] Preferably, the mass of the polyvinyl alcohol is 8-15% of the mass of the material after drying, for example, 8%, 10%, 11%, 12% or 15%.
[0042] Preferably, the sintering temperature is 950-1000°C, for example, 950°C, 960°C, 970°C, 980°C or 1000°C.
[0043] Preferably, the sintering time is 6 to 8 hours, for example, 6 hours, 6.5 hours, 7 hours, 7.5 hours or 8 hours.
[0044] In a second aspect, the present invention provides a soft magnetic composite ferrite core, which is manufactured by the method described in the first aspect.
[0045] Preferably, the grain size of the soft magnetic composite ferrite core is 2-4 μm, for example, 2 μm, 2.5 μm, 3 μm, 3.5 μm or 4 μm.
[0046] Preferably, the specific temperature coefficient of the soft magnetic composite ferrite core is less than 3×10 -6 .
[0047] Preferably, the specific temperature coefficient of the soft magnetic composite ferrite core in the range of -40°C to 140°C is less than 3×10 -6 .
[0048] Preferably, the Curie temperature of the soft magnetic composite ferrite core is >200°C.
[0049] In a third aspect, the present invention provides an inductor device, wherein the inductor device comprises the soft magnetic composite ferrite core as described in the second aspect.
[0050] Compared with the prior art, the present invention has the following beneficial effects:
[0051] (1) In the preparation process of the soft magnetic composite ferrite core of the present invention, manganese oxide and copper oxide are used to replace nickel oxide, so that the cost of raw materials is reduced. Through two-step pre-sintering, copper oxide can react with iron oxide to form CuFe 2 O 4 , manganese oxides react with iron oxides to form spinel MnFe 2 O 4 It can promote the subsequent sintering reaction and effectively reduce the sintering temperature. Due to the low sintering temperature, a lot of energy is saved, the design requirements of sintering equipment are also reduced, and the production cost is further reduced. Due to the wide pre-sintering and sintering temperature range and the absence of atmosphere protection, the process repeatability and product consistency are very good.
[0052] (2) The μi of the soft magnetic composite ferrite core prepared by the method of the present invention can reach above 1514, and the specific temperature coefficient within -20 to 65°C can reach 2.722×10 -6 Below, the specific temperature coefficient within -40℃~140℃ can reach 2.94×10 -6 Below, the Curie temperature can reach above 205℃ and the saturation magnetic induction intensity Bs can reach above 442mT. DETAILED DESCRIPTION
[0053] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0054] Example 1
[0055] This embodiment provides a soft magnetic composite ferrite core, and the preparation method of the soft magnetic composite ferrite core is as follows:
[0056] (1) According to Fe 2 O 3 52.5mol%; ZnO 28mol%: CuO 6.25mol%: Mn 3 O 4 3 mol%; Ni 2 O 3The main material is weighed to be 10.25 mol%, and the main material is put into a ball mill, and deionized water of equal weight is added, and the ball mill is performed for 5 hours. The mixed main material is dried, and then pre-fired at 700°C for 2 hours and then at 850°C for 1.5 hours to obtain a pre-fired material. The pre-fired material is subjected to XRD phase analysis to determine that only spinel structure exists in the pre-fired material without other impurity phases;
[0057] (2) The pre-sintered material and Bi 2 O 3 and SnO 2 Mixed (where the mass of the main material is 100%, Bi 2 O 3 The mass is: 0.24wt%, SnO 2 The mass of Bi is: 0.03wt%, 2 O 3 and SnO 2 The weight percentage is 1:0.125), the mixed material is put into a ball mill, and an equal weight of deionized water is added, and the ball mill is performed for 12 hours to make the average particle size of the pre-sintered material less than 1 μm. After drying, 10 wt% of polyethylene ethanol (PVA) is added, and the mixture is uniformly mixed, and a 45-mesh sample sieve is used for granulation, and the mixture is pressed into The sample ring is placed in a box-type furnace for sintering, the sintering temperature is controlled at about 965° C., the holding time is 6 hours, and the furnace is cooled to room temperature to obtain the soft magnetic composite ferrite core.
[0058] Example 2
[0059] This embodiment provides a soft magnetic composite ferrite core, and the preparation method of the soft magnetic composite ferrite core is as follows:
[0060] (1) According to Fe 2 O 3 55.6mol%; ZnO 26.6mol%; CuO 5.1mol%; MnO 3.2mol%; Ni 2 O 3 The main material is weighed at 9.5 mol%, and the main material is put into a ball mill, and deionized water of equal weight is added, and the ball mill is performed for 5 hours. The mixed main material is dried, and then pre-fired at 680°C for 2.5 hours and then at 800°C for 3 hours to obtain a pre-fired material. The pre-fired material is subjected to XRD phase analysis to determine that only spinel structure exists in the pre-fired material without other impurity phases;
[0061] (2) The pre-sintered material and Bi 2 O 3 and SnO 2 Mixed (where the mass of the main material is 100%, Bi 2 O 3The mass is: 0.4wt%, SnO 2 The mass of Bi is: 0.1wt%, 2 O 3 and SnO 2 The weight percentage is 1:0.25), the mixed material is put into a ball mill, and an equal weight of deionized water is added, and the ball mill is performed for 10 hours to make the average particle size of the pre-burned material less than 1μm. After drying, 10wt% of polyethylene ethanol (PVA) is added, and the mixture is evenly mixed, and a 45-mesh sample sieve is used for granulation, and the mixture is pressed into The sample ring is placed in a box-type furnace for sintering, the sintering temperature is controlled at about 950° C., the holding time is 6 hours, and the furnace is cooled to room temperature to obtain the soft magnetic composite ferrite core.
[0062] Example 3
[0063] This embodiment provides a soft magnetic composite ferrite core, and the preparation method of the soft magnetic composite ferrite core is as follows:
[0064] (1) According to Fe 2 O 3 53.7mol%; ZnO 31mol%; CuO 3.82mol%; Mn 3 O 4 2mol%; Ni 2 O 3 The main material is weighed to be 9.48 mol%, and the main material is put into a ball mill, and an equal weight of deionized water is added, and the ball mill is performed for 5 hours. The mixed main material is dried, and then pre-fired at 720°C for 1 hour, and then pre-fired at 900°C for 1 hour to obtain a pre-fired material. The pre-fired material is subjected to XRD phase analysis to determine that only spinel structure exists in the pre-fired material, and no other impurity phases;
[0065] (2) The pre-sintered material and Bi 2 O 3 and SnO 2 Mixed (where the mass of the main material is 100%, Bi 2 O 3 The mass is: 0.6wt%, SnO 2 The mass of Bi is: 0.1wt%, 2 O 3 and SnO 2 The weight percentage is 1:0.1667), the mixed material is put into a ball mill, and an equal weight of deionized water is added, and the ball mill is performed for 12 hours to make the average particle size of the pre-burned material less than 1μm. After drying, 10wt% of polyethylene ethanol (PVA) is added, and the mixture is evenly mixed, and a 45-mesh sample sieve is used for granulation, and the mixture is pressed into The sample ring is placed in a box-type furnace for sintering, the sintering temperature is controlled at about 1000° C., the insulation time is 6 hours, and the furnace is cooled to room temperature to obtain the soft magnetic composite ferrite core.
[0066] Example 4
[0067] The difference between this embodiment and embodiment 1 is that the main material composition is: Fe 2 O3 is 54.4 mol%; ZnO is 29.57 mol%; CuO is 3.33 mol%; Mn 3 O 4 2.7 mol%; Ni 2 O 3 The additive is Bi 2 O 3 0.24wt%, SnO 2 The other conditions and parameters are exactly the same as those in Example 1.
[0068] Example 5
[0069] The difference between this embodiment and embodiment 1 is that the main material composition is: Fe 2 O3 is 52.8mol%; ZnO is 33.5mol%; CuO is 2.85mol%; Mn 3 O 4 1.4 mol%; Ni 2 O 3 9.45 mol%, additive is Bi 2 O 3 0.24wt%, SnO 2 The other conditions and parameters are exactly the same as those in Example 1.
[0070] Example 6
[0071] The only difference between this embodiment and embodiment 1 is that the temperature of the one-step pre-firing is 650° C., and the other conditions and parameters are exactly the same as those in embodiment 1.
[0072] Example 7
[0073] The only difference between this embodiment and embodiment 1 is that the temperature of the one-step pre-firing is 750° C., and the other conditions and parameters are exactly the same as those in embodiment 1.
[0074] Example 8
[0075] The only difference between this embodiment and embodiment 1 is that the temperature of the second-step pre-firing is 750° C., and the other conditions and parameters are exactly the same as those of embodiment 1.
[0076] Example 9
[0077] The only difference between this embodiment and embodiment 1 is that the temperature of the second-step pre-firing is 950° C., and the other conditions and parameters are exactly the same as those of embodiment 1.
[0078] Example 10
[0079] The difference between this embodiment and embodiment 1 is that the additive is only nano Bi. 2 O 3 , other conditions and parameters are exactly the same as those in Example 1.
[0080] Embodiment 11
[0081] The difference between this embodiment and embodiment 1 is that only submicron SnO is added as an additive. 2 , other conditions and parameters are exactly the same as those in Example 1.
[0082] Comparative Example 1
[0083] The only difference between this comparative example and Example 1 is that the pre-sintering is performed at 800° C., and the other conditions and parameters are exactly the same as those in Example 1.
[0084] Comparative Example 2
[0085] The only difference between this comparative example and Example 1 is that no manganese oxide is added, and other conditions and parameters are exactly the same as those in Example 1.
[0086] Comparative Example 3
[0087] The only difference between this comparative example and Example 1 is that copper oxide is not added, and other conditions and parameters are exactly the same as those in Example 1.
[0088] Performance Testing:
[0089] The magnetic properties of the samples obtained in the embodiments and comparative examples were tested, and the test results are shown in Table 1:
[0090] Table 1
[0091]
[0092]
[0093] As can be seen from Table 1, from Examples 1 to 5, the μi of the soft magnetic composite ferrite core prepared by the method of the present invention can reach more than 1514, and the specific temperature coefficient within -20 to 65°C can reach 2.722×10 -6 the following,
[0094] The specific temperature coefficient within -40℃~140℃ can reach 2.94×10 -6 Below, the Curie temperature can reach above 205℃ and the saturation magnetic induction intensity Bs can reach above 442mT.
[0095] By comparing Example 1 with Examples 6-7, it can be seen that in the preparation process of the soft magnetic composite ferrite core of the present invention, the temperature of the one-step pre-burning will affect its performance. The temperature of the one-step pre-burning is controlled at 680-720°C to obtain a core with better performance. If the temperature of the one-step pre-burning is too low, the magnetic permeability of the core will decrease, and the specific temperature coefficient of the material will increase; the stability of the core will deteriorate. If the temperature of the one-step pre-burning is too high, the magnetic permeability of the core will decrease, the saturation magnetization intensity of the core will deteriorate, and the stability of the material will deteriorate.
[0096] By comparing Example 1 with Examples 8-9, it can be seen that in the preparation process of the soft magnetic composite ferrite core of the present invention, the temperature of the two-step pre-burning will affect its performance. The temperature of the two-step pre-burning is controlled at 800-900°C to obtain a core with better performance. If the temperature of the two-step pre-burning is too low, the core will crack due to severe deformation, the magnetic permeability of the core will be reduced, and the saturation magnetic induction intensity Bs will also be reduced. If the temperature of the two-step pre-burning is too high, the material particle size will be difficult to grind, and then the magnetic permeability will be reduced, and the magnetic saturation induction intensity Bs will be reduced, so the temperature coefficient will increase.
[0097] By comparing Example 1 with Examples 10-11, it can be seen that the present invention uses nano Bi 2 O 3 and submicron SnO 2 As an additive, Bi 2 O 3 The powder has a nanometer size, a large specific surface area, and a relatively high surface energy. It can form a liquid phase at a very low temperature, promote sintering, and effectively reduce the sintering temperature. Using an appropriate amount of submicron SnO 2 As a flux, although it can improve high-frequency characteristics, it reduces the quality factor of the low-frequency band; and the appropriate amount of Bi 2 O 3 The addition of flux is the opposite, which is beneficial to reducing the loss in the low frequency band, but not conducive to reducing the loss in the high frequency band. Moreover, although the single flux addition method can reduce the sintering temperature to a certain extent, the effect is not as good as Bi. 2 O 3 and SnO 2 The quality factor of ferrite decreases with the increase of the added amount. 2 O 3 and submicron SnO 2 The combined addition as an additive flux can effectively reduce the sintering temperature to below 1100°C, and both high-temperature and low-temperature magnetic permeabilities are greatly improved, with good temperature stability characteristics.
[0098] By comparing Example 1 with Comparative Examples 1-3, it can be seen that in the preparation process of the soft magnetic composite ferrite core of the present invention, manganese oxide and copper oxide are used to replace nickel oxide, so that the cost of raw materials is reduced. In the one-step pre-sintering process, copper oxide can form CuFe with iron oxide. 2 O 4 , so that spinel ferrite can be formed at a very low temperature, and manganese oxide and iron oxide form spinel MnFe during the two-step pre-sintering process. 2 O 4 This is very beneficial for promoting the subsequent sintering reaction and can effectively reduce the sintering temperature. Due to the low sintering temperature, a lot of energy is saved, the design requirements of the sintering equipment are also reduced, and the production cost is further reduced. Due to the wide pre-sintering and sintering temperature range and the absence of atmosphere protection, the process repeatability and product consistency are very good.
[0099] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a soft magnetic composite ferrite core, characterized in that: The preparation method comprises the following steps: (1) grinding and mixing the main materials and then pre-burning them to obtain a pre-burned material; (2) mixing the pre-sintered material with the additive, grinding it, and then performing a molding and sintering process to obtain the soft magnetic composite ferrite core; The main materials include iron oxide, zinc oxide, nickel oxide, manganese oxide and copper oxide, and the pre-firing process includes one-step pre-firing and two-step pre-firing.
2. The preparation method according to claim 1, characterized in that The iron oxide includes Fe2O3; Preferably, the zinc oxide comprises ZnO; Preferably, the nickel oxide comprises Ni2O3; Preferably, the manganese oxide comprises MnO and / or Mn3O4; Preferably, the copper oxide comprises CuO; Preferably, based on the molar amount of the main material being 100%, the molar fraction of the iron oxide is 52.5 to 55.6 mol%; Preferably, based on the molar amount of the main material being 100%, the molar fraction of the zinc oxide is 26.5 to 34 mol%; Preferably, based on the molar amount of the main material being 100%, the molar fraction of the nickel oxide is 9 to 12 mol%; Preferably, based on the molar amount of the main material being 100%, the molar fraction of the manganese oxide is 1.4 to 3.5 mol%; Preferably, based on 100% of the molar amount of the main material, the molar fraction of the copper oxide is 2-8 mol%.
3. The preparation method according to claim 1 or 2, characterized in that: The grinding and mixing method in step (1) includes ball milling; Preferably, the grinding and mixing time is 2 to 4 hours; Preferably, the mixed material is dried after the grinding and mixing.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The temperature of the one-step pre-burning is 680-720°C; Preferably, the one-step pre-burning time is 1 to 3 hours; Preferably, the temperature of the second-step pre-firing is 800-900°C; Preferably, the second-step pre-burning time is 1 to 3 hours.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The additives in step (2) include nano Bi2O3 and submicron SnO2; Preferably, based on the mass of the main material being 100%, the mass of the Bi2O3 is 0.1 to 2.5%; Preferably, based on the mass of the main material being 100%, the mass of the SnO2 is 0.03-0.5%; Preferably, the mass ratio of Bi2O3 to SnO2 is 1:(0.1-1.2).
6. The preparation method according to any one of claims 1 to 5, characterized in that: The grinding process in step (2) includes ball milling; Preferably, the grinding treatment time is 3 to 15 hours; Preferably, the average particle size of the material obtained after the grinding process is less than 1 μm.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The molding and sintering treatment in step (2) includes drying the ground material, mixing it with polyvinyl alcohol, pressing it into shape, and then sintering it to obtain the soft magnetic composite ferrite core; Preferably, the mass of the polyvinyl alcohol is 8-15% of the mass of the material after drying; Preferably, the sintering temperature is 950-1000°C; Preferably, the sintering time is 6 to 8 hours.
8. A soft magnetic composite ferrite core, characterized in that: The soft magnetic composite ferrite core is obtained by the method according to any one of claims 1 to 7.
9. The soft magnetic composite ferrite core according to claim 8, characterized in that: The grain size of the soft magnetic composite ferrite core is 2 to 4 μm; Preferably, the specific temperature coefficient of the soft magnetic composite ferrite core is less than 3×10 -6 ; Preferably, the specific temperature coefficient of the soft magnetic composite ferrite core in the range of -40°C to 140°C is less than 3×10 -6 ; Preferably, the Curie temperature of the soft magnetic composite ferrite core is >200°C.
10. An inductor device, characterized in that: The inductor device comprises the soft magnetic composite ferrite core as claimed in claim 8 or 9.
Citation Information
Patent Citations
Composite soft magnetic material and method for preparing material
CN103632794A
Magnetic core and preparation method thereof, inductor and filter
CN111584206A